Wartość natury kreowana na nagrodzonych fotografiach World Press Photo w II dekadzie XXI wieku. Analiza socjologiczna - Błażej, Mariola (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The article rests on an assumption that the way people perceive and conceptualize the world is largely influenced by culture, society and the processes of socialization. In this context, the authors focus on the issue of “everyday life reality,” which is of particular interest to the sociology of knowledge and the phenomenological sociology of Peter Berger and Thomas L. Luckmann. The article aims to show how the authors of photographs awarded in the World Press Photo competition in the second decade of the 21st century in the category Nature construct the value of the natural world as an endangered resource. The second objective is to present the potential of visual message analysis from the perspective of qualitative sociology. The way in which the objectives are pursued is consistent with the theoretical underpinnings of phenomenological sociology and carried out within the methodological framework developed in the field of visual sociology. The article’s subject matter stems from the belief that in today’s visual communication culture, conveying information through images involves valuation processes. The article discusses 10 photos that were awarded 1st place in the prestigious World Press Photo competition in the category Nature in the second decade of the 21st century. An analysis of the photos leads to a conclusion that the descriptions of the photos provided by their authors create a negative image of a human being, juxtaposed against the good and defenceless world of nature.